Improcedencia del abandono en materia penal al no existir el oportuno despacho a las solicitudes de las partes. - Valencia Guillen, Henrry Patricio (2018)
The present research paper whose theme is "IMPROCEDENCE OF ABANDONMENT IN CRIMINAL MATTERS, SINCE THERE IS NO TIMELY DELIVERY TO THE REQUESTS OF THE PARTIES", the objective of this research work is oriented to the legal and critical analysis of the procedures and Demands for the application of the functions of the Office of the Prosecutor, as well as establishing a legal reform to the Integral Criminal Code, for addressing an issue of the legal and social reality of Ecuador, by allowing the process to be abandoned if it does not comply with all its Proceedings. The current criminal legislation that governs social activity in Ecuador, establishes in the new Organic Code Comprehensive Criminal several novel figures that are applied through the accusatory oral system, but regarding the abandonment in the causes of private action, these regulations evidence failures The same ones that violate principles and constitutional guarantees, as I allow to expose next. Article 651 of the Comprehensive Criminal Organic Code establishes that abandonment will occur if the complainant stops impelling it for thirty days, counted from the last petition or complaint made to the judge, which in practice entails that the complainant is obliged to file Unofficial writings periodically on pain of the cause falling into lethargy and therefore for no other reason than the alleged lack of momentum for more than 30 days, the judge can dictate abandonment of the case and the consequent file of the same without there being At least the possibility that such a decision may be appealed. Unfortunately, the Judiciary of Criminal Guarantees in Ecuador, far from carrying out a legal and constitutional analysis of the scope of this norm, dictate the abandonment of criminal cases without further reasoning of the calculations of the 30 days without presentation of writs by the complainant which In my view, clearly violates the constitutional principle of legal certainty and defense. It is very common in practice that the complainant submits petitions in order to give real impetus to the procedure proper to private action depending on the state of the case, petitions that usually do not deserve the timely dispatch within 30 days, making That this breach of the obligations of the judicial servers, are attributable to the complainants because such irresponsibility in theory generates the abandonment of the cause even if it is incredible or inexplicable. The legal problem exposed causes violations of the most basic rights and constitutional guarantees of the procedural parties and fundamentally those who have access to justice in order to enforce the recognition of their rights before the court. The present thesis of Legal Investigation is structured as follows: First, a Conceptual Framework, which includes concepts and definitions of the Sanctions, conditional suspension, among other concepts that will give greater emphasis to the proposed topic; A Doctrinal Framework, which covers the doctrines of writers and scholars on how they obtain conditional suspension of sentence. Legal Framework, which includes the analysis of the Constitution of the Republic of Ecuador, the Comprehensive Criminal Organic Code, the Organic Code of Judicial Function and then we have a Comparative Legislation, since it served me to carry out an analysis of the matter of other countries And to extract the most positive. Secondly the research work comprises a field study in which surveys and interviews are developed to those who know the law in which they help me to determine or contrast the objectives and hypotheses raised. In the third place after the analysis of the field research, the conclusions and recommendations were made and finally a legal proposal necessary to solve the problem.